2016
DOI: 10.1177/1467358415610375
|View full text |Cite
|
Sign up to set email alerts
|

A study of festival switching intentions, festival satisfaction, festival image, festival affective impacts, and festival quality

Abstract: There is a conceptual gap in the marketing literature, as to date there has been no published empirical research on festival switching intentions, festival satisfaction, festival image, festival affective impacts, and festival quality that have focused in the context of food festivals. This study seeks to fill this conceptual gap by identifying the dimensions of festival quality and empirically examining the interrelationships among festival switching intentions, festival satisfaction, festival image, festival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
55
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 134 publications
(327 reference statements)
9
55
3
2
Order By: Relevance
“…To develop satisfaction items, a number of authors were considered (Albayraka & Caberb, 2018;Son & Lee, 2011;Wan & Chan, 2013;Wu & Ai, 2016;Wu et al, 2014;Yoon et al;2010). The service satisfaction was evaluated by 11 items, among them, Table 1.…”
Section: 2) Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…To develop satisfaction items, a number of authors were considered (Albayraka & Caberb, 2018;Son & Lee, 2011;Wan & Chan, 2013;Wu & Ai, 2016;Wu et al, 2014;Yoon et al;2010). The service satisfaction was evaluated by 11 items, among them, Table 1.…”
Section: 2) Measuresmentioning
confidence: 99%
“…In Portugal and Spain, many regions have become part of many tourist's itinerary because they host cultural events of performing arts, such as music and dance Several studies about festivals (Baker & Crompton, 2000;McDowall, 2011;Son & Lee, 2011;Stankova & Vassenska, 2015;Wan & Chan, 2013;Wu & Ai, 2016;Yoon et al, 2010), showed that festival participants' experience is commonly assessed through perceived quality and satisfaction, factors that may influence future behavioural intentions (revisit intention and intention to recommend). In addition, since motivation is the basis of the desire to experience something, motivation can be considered as one of the fundamental elements of the entire tourism process, the starting point of the entire touristic and experiential journey of the individual.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sistemler teorisine göre, girdi sürecinde yer alan gerekli kaynakların başarı algısını oluşturacağı, çıktı sürecinde ise sadakatin meydana geleceği ileri sürülmektedir. Festival sadakatinin, başarı faktörleri tarafından gerçekleşebileceği belirtilebilir (Anil, 2012;Wu ve Ai, 2016;Lee ve Chang, 2017). Bu bağlamda bu çalışmada, festival anahtar başarı faktörlerinin festival sadakati üzerindeki etkisi araştırılmıştır.…”
Section: Introductionunclassified